Pengaruh Pelatihan dan Beban Kerja terhadap Kinerja Karyawan Pramusapa pada PT Transjakarta - Aisy, Naurah Rahadatul; H. Fikriah; Sekarini, Ratih Ayu (Jurnal Ekonomi Bisnis Manajemen Prima, 2025)
This study aims to test and analyze the Influence of Training and Workload on the Performance of Pramusapa Employees at PT Transjakarta. To analyze the influence between independent variables and dependent variables. With the independent variables being Training and Workload, while the dependent variable is Employee Performance, using a quantitative approach. Data collection was carried out using random sampling techniques. From a total population of 1,554 Pramusapa, a sample of 85 was taken using the Slovin formula with a margin of error of 10%. Data distribution using a questionnaire via Google Form and data testing was carried out using SmartPLS version 4.1. The results of the R Square value is 0.674, which means that the influence of the independent variable on the dependent variable is 67.4% and the remaining 32.6% is influenced by other variables outside the model studied by the author. The results of this study state that: (1) Training and Workload have an effect on Employee Performance; (2) Training has an effect on Employee Performance; (3) Workload has an effect on Employee Performance.